Effects of interactive games on motor performance in children with spastic cerebral palsy - AlSaif, Amer A. (J Phys Ther Sci, 2015)
[Purpose] Motor control and muscle strength impairments are the prime reasons for motor behavior disorders in children with spastic cerebral palsy. These impairments lead to histological changes in muscle growth and the learning of motor skills. Therefore, such children experience reduced muscle force generation and decreased muscle flexibility. We investigated the effect of training with Nintendo Wii Fit games on motor performance in children with spastic cerebral palsy. [Subjects and Methods] Forty children with cerebral palsy spastic diplegia aged 6–10 years diagnosed with level-3 functional capabilities according to the Gross Motor Classification System (GMFCS) were enrolled. Participants were divided randomly into equal groups: group (A) that practiced with the Nintendo Wii Fit game for at least 20 minutes/day for 12 weeks and group (B) that underwent no training (control group). The Movement Assessment Battery for Children-2 (mABC-2) was used to assess motor performance, because it mainly involves motor tasks very similar to those involved in playing Nintendo Wii Fit games, e.g., goal-directed arm movements, balancing, and jumping. [Results] There were significant improvements in the subscales of the motor performance test of those who practiced with the Nintendo Wii, while the control group showed no significant changes. [Conclusion] Using motion interactive games in home rehabilitation is feasible for children with cerebral palsy.